HO CHI MINH’S THOUGHT ON MASS MOBILIZATION AND THE APPLICATION OF THIS VIEW BY THE COMMUNIST PARTY OF VIETNAM IN CURRENT SITUATION - Pham, Ngoc Loi (American International Journal of Social Science Research, 2021)
Over half a century ago, President Ho Chi Minh gave a basic thought about the mobilization work of a revolutionary Party in a famous article published in the newspaper "The Truth" (Su That). That work is considered as the platform for the work of mass mobilization. His thoughts have led our Party to implement the mobilization work to achieve great achievements, decisive to the victory of our revolution during the past 71 years. This study aims to analyze President Ho Chi Minh’s thoughts on mass mobilization. The author used scientific research methods such as analysis and synthesis, interpretation and induction, abstraction and generalization, logic and history, and comparison to come to conclusions and general judgment. The study focused on clarifying the contents of Ho Chi Minh's Thoughts on mass mobilization and the application of the Communist Party of Vietnam in current conditions.